Unifying EU representation at the IMF executive board: A voting and veto power analysis - Peter Brandner; Harald Grech; Iain Paterson (Institute for Advanced Studies (IHS), 2009)
The consequences of consolidating EU representation at the IMF Executive Board by regrouping the 27 Member States into two EU constituencies, euro area and non-euro area, are discussed. In particular we contrast voting power as proposed by Penrose-Banzhaf (PBI) and Shapley-Shubik (SSI), and other respectively related measures of blocking (or veto) power and decision efficiency as proposed by Coleman and Paterson. Hitherto, IMF-specific literature is PBI-based. However, theoretical reasons and empirical plausibility arguments for the SSI are compelling. The (SSI) voting power of the two large constituencies - U.S.A. and euro area - reflects their corresponding voting shares over a range of majority thresholds, whereas PBI voting power reduces to only half of vote share at the majority threshold of 85% needed for some Executive Board decisions. SSI-related estimates of veto power are generally lower than the Coleman indices. Correspondingly, the efficiency of collective decision-making is considerably underestimated by the Coleman measure.
Keywords: C71; D71; 330; International Monetary Fund; European Union; voting power analysis; veto power; Internationale Wirtschaftsorganisation; Mitgliedschaft; Politische Entscheidung; Veto; EU-Staaten; Spieltheorie